2006
DOI: 10.1007/s10194-006-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of primary headache symptoms at school-entry: a population-based epidemiological survey of preschool children in Germany

Abstract: Primary headache and functional abdominal pain prevalences in an unselected populationbased sample of German preschool children and their parents (n=885) were collected in relation to health-related quality of life and sociodemographic variables. The pain symptoms were assessed according to IHS classification (2004) and Rome-II criteria (1999) during the 2004 data census. The participation rate was 62.7%, with an equal gender distribution. The focus of this paper lies on the symptom-oriented point prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
5
13
0
2
Order By: Relevance
“…Therefore only 3.6% of this sample suffered from recurrent headache, with a boy/girl ratio of 10 to 1 [3]. Along with this finding, in outpatient headache sufferers under 6 years of age, a greater male gender prevalence and shorter duration of headache attacks were reported [4].…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Therefore only 3.6% of this sample suffered from recurrent headache, with a boy/girl ratio of 10 to 1 [3]. Along with this finding, in outpatient headache sufferers under 6 years of age, a greater male gender prevalence and shorter duration of headache attacks were reported [4].…”
supporting
confidence: 54%
“…The study of Ostkirchen et al [3] examined the prevalence of primary headache and functional abdominal pains in 555 preschool children assessed by a self-administered questionnaire. In this issue the Authors reported that 85.6% of the sample suffered from pain, mainly abdominal pains (33.2%), often associated with headache (48.8%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most researches have been devoted to studying schoolchildren and adolescents. Studies focused on preschool children are scarce [14,15,38]. Since research suggests that somatic symptoms in adults have their origins in childhood and maintain certain continuity [3,9,18,34], it seems important to verify the presence of symptoms at early ages.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is higher than in our study and could be due to the older age of the children. Also, parents seem to underestimate the intensity of the headache in their preschool children …”
Section: Discussionmentioning
confidence: 99%